ENVIRONMENTAL EXERGY ANALYSIS OF WASTEWATER TREATMENT PLANTS - Mora, C. B. H.; de Oliveira Jr, S. (Revista de Engenharia Térmica, 2006)
This work evaluates the environmental impact of Wastewater Treatment Plants (WTP) based on data generated by the exergy analysis, calculating and applying environmental impact indexes for two WTP located in the Metropolitan Area of São Paulo. The environmental impact of the waste water treatment plants was done by means of evaluating two environmental impact exergy based indexes: the environmental exergy efficiency (ηenv,exerg) and the total pollution rate (Rpol,t). The environmental exergy efficiency is defined as the ratio of the exergy of the useful effect of the WTP to the total exergy consumed by human and natural resources, including all the exergy inputs. That relation is an indication of the theoretical potential of future improvements of the process. Besides the environmental exergy efficiency, it is also used the total pollution rate, based on the definition done by Makarytchev (1997), as the ratio of the destroyed exergy associated to the process wastes to the exergy of the useful effect of the process. The analysis of the results shows that this method can be used to quantify and also optimise the environmental performance of Wastewater Treatment Plants.